Exploring the Evolution of Modern English: Philological Perspectives on Literary Transformations - Ismailov Salaxiddin Ismailovich (Euro Asian Journal Publishing, 2024)
This article investigates the evolution of Modern English through a philological perspective, emphasizing significant literary transformations that have influenced its development. It traces the progression from Early Modern English to contemporary usage, assessing the impact of historical, social, and cultural factors. Through an exhaustive literature review, this study amalgamates existing research on phonological, morphological, syntactic, and lexical changes. Utilizing qualitative analysis of seminal literary texts, the research elucidates the dynamic interaction between language and literature. The findings highlight the crucial role of literary works in both reflecting and shaping linguistic evolution, providing insights into the ongoing transformation of Modern English.
Keywords: Modern English; philology; literary transformations